Engineering nanoparticles using chemical and biological approaches for tumor targeted delivery - Nguyen, Tuyen Duong Thanh (Kansas State University, 2019)
Nanotechnology offers exciting options for the site-selective delivery of chemotherapeutics and diagnostic agents using nanoparticles. Varieties of organic and inorganic nanomaterials have been explored extensively as a delivery system either in the form of drug carriers or imaging agents. Successful stories include the clinical translation of anticancer nanomedicines such as PEGylated liposomal doxorubicin (DOXIL®), albumin-bound paclitaxel (Abraxane®), and polymeric micelle loaded paclitaxel (Genexol®), which are currently used in the clinic as one of the first lines for cancer chemotherapies. These conventional nanomedicines rely on passive-drug targeting taking advantage of leaky tumor vasculature, called the Enhanced Permeability and Retention (EPR) effect. However, delivering biologically active components selectively to the diseased cell, for example, cancer, is highly challenging due to the biological barriers in the body including blood pool cells/proteins, heterogeneous microenvironment, and intracellular degradation. Therefore, the goal of this dissertation is to develop nanoplatforms that can deliver the agents of interest in targeted fashion to cancer while bypassing or collaborating with the biological barriers. The design consideration of these nanoplatforms centralizes on using simple chemical reactions and cell biology to engineer nanoparticles. The presented nanoparticles were extensively studied and evaluated for their biological functions using in vitro and in vivo models. These nanoconstructs described herein address current limitations of conventional nanomedicine such as (1) the lack of understanding of the interaction of nanoparticle and biological system, and (2) the lack of an effective targeting strategy to deliver drugs to the cancer cell in the tumors. The significant findings of each system will be highlighted and discussed throughout this dissertation. Results obtained highlight key findings such as NP intracellular fate, maximized tumor accumulation, and unique pharmacokinetics could open the avenues for systemic investigations for personalized medicine and lay the foundation for nanomedicine design to accelerate clinical translation.
Keywords: Nanomedicine; MRI contrast agents; Biomimetic; Cancer; Targeted delivery; Polymeric nanoparticles